Arthrospira (Spirulina) platensis for protein products - Faustino, Isabel Maria Serpa Branco (2019)
The still growing world population naturally raises a concern about the existence of food to satisfy the human feeding needs. However, conventional means of food production cause major environmental pollution impacts, such as greenhouse gas emissions, excessive use of arable land and significant water footprints. In this way, microalgae emerge as a promising alternative of protein supply for future generation. The present work, shows the laboratory-scale results of two Arthrospira (Spirulina) platensis biorefinery proposals for the production of a color-free protein extract which is applicable to food industry, and simultaneously an isolated fraction of phycocyanin, which is a pigment of high commercial value, and lipid and carbohydrate extracts are also produced. In order to meet the requirements of the food industry, extractions were tested using non-toxic solvents for protein and phycocyanin extraction and for lipid extraction. In order to separate phycocyanin from other soluble proteins an aqueous two-phase system was tested, which is an innovative biocompatible two-phase separation technique suitable for the food industry. Subsequently, the laboratory results were extrapolated for mass balance calculations in order to select the best biorefinery proposal through a technical-economic analysis. The proposal for Spirulina biorefinery using the two-phase aqueous system for the extraction and prepurification of phycocyanin, at the same time, proved to be the most promising process for future studies, since, this process had the lower estimated CAPEX and the purity of the phycocyanin fraction obtained is included in the food grade, the two-phase aqueous system having two aqueous phases has beneficial effects for the application of recovered protein products to human food.